Geodiversity and Occupation of Space—Physical Geography, Human Geography Interface: The Example of the Chapada Diamantina, Bahia, Brazil - Giudice, Dante Severo (2022)
The article aims to describe the Physical Geography, Human Geography interface, based on the concept of geodiversity, closely related to geomorphology and geology, which encompasses geological heritage, and its importance in the occupation of space and in territorial logics, through Geoconservation and Geotourism.